Dynamic of changes in the level of Interleukin 1B against the background of the development of experimental diabetic retinopathy and under the influence of various methods of correction - Sirman, Y.; Savytskyi, I.; Preys, N.; Blavatska, O. (Journal of Education, Health and Sport, 2022)
The aim of our research is investigating the changes in the level of interleukin 1β in experimental animals, which were simulated diabetic retinopathy and against the background of its correction. The obtained indicate that already on the 30th day of the development of experimental diabetic retinopathy, a significant increase in the pro-inflammatory cytokine level draws attention. Analyzing the data of group No. 3, it was established that the correction of the pathological condition with hypoglycemic agents has a positive effect but requires the involvement of additional means of correction in addition to the normalization of the level of glycemia. The results of the 4th experimental group indicate that the involvement of a nitric oxide donor and aflibercept in the correction of diabetic retinopathy has a positive effect on the reduction of the level of Interleukin 1β, but it does not reach an approximation to the norm. It is observed that the correction of the simulated pathological condition by reducing hyperglycemia, administration of aflibercept and bromfenac (group No. 5) gives positive results, but less pronounced than involvement in the complex correction of L-arginine solution in the study of nitric oxide synthases, in the analysis of the pro-inflammatory cytokine level the results are better. It is also worth noting that this method of correction is not characterized by longevity and on the 180th day there is already a pronounced decrease in its effectiveness. It was found that in rats in which diabetic retinopathy was modeled with subsequent correction of hyperglycemia, administration of aflibercept, L-carnitine and bromfenac (group No. 6), there is a pronounced effectiveness of the proposed method of correction in comparison with the previously considered methods. As for the correction applied in the 7th group, in the first and second stages, the inflammation indicator is more elevated compared to the two previous groups (No. 5 and No. 6), but in the third stage, a marked decrease in the level of the marker was established, which indicates the effectiveness of the correction of the 7th group at more distant stages of the experiment.